The Existence of the Role of Headman in Marriage Registration on the Case of an Adoptive Father in a Birth Certificate - Rusdiman Suaib; Ajub Ishak (Al-Mizan (e-Journal), 2018)
The problem in this study is how the existence of the Headman's existence in the registration of marriage for the adoptive father's case in the birth certificate of the child to be married. This research is a qualitative descriptive study with a juridical approach. The results showed that the existence of the Headman's role was not optimal because there were still some obstacles, including the character of the community who did not know the recording procedure and the lack of understanding of marital law, especially regarding the issue of adopted children who were attributed to adoptive fathers who according to Islamic law were not justified, but the facts showed so many adopted children born ascribed to adoptive fathers and influence the registration of marriage, especially guardians for adopted children.